PENGEMBANGAN MEDIA PEMBELAJARAN BERDASARKAN KONSEP TPACK PADA MATERI GARIS DAN SUDUT MENGGUNAKAN HAWGENT DYNAMIC MATHEMATICS SOFTWARE - Tommy Tanu Wijaya; Aditya Purnama; Hendry Tanuwijaya (IKIP Siliwangi, 2020)
At every level of education, one of the most important lessons is mathematics. Mathematics becomes a very important learning because it is always used in everyday life. Therefore mathematics learning must be centered on the basic concepts of mathematics. So students can apply the basic concepts of mathematics to everyday life. At this time the development of technology is very rapid and can be utilized to develop based on the TPACK concept of learning media that is in accordance with the model or learning approach to explain a mathematical concept. So that learning mathematics can be more interesting and can help students to understand the basic concepts of mathematics. Hawgent is one of the software developed in accordance with the needs of teaching mathematics. In this study learning media will be developed based on the TPACK concept on line and angle material using hawgent dynamic mathematics software. The results of this study are learning media declared valid by media experts and material experts and can be implemented in schools.